The effect of offline tDCS targeting the dorsolateral prefrontal cortex on maximum exertion endurance performance - Vainio, Ville; Vihervuori, Marianne (2024)
The dorsolateral prefrontal cortex (DLPFC) plays a crucial role in cognitive functions and may impact physical endurance. Anodal transcranial direct current stimulation (a-tDCS) is a non-invasive brain stimulation technique (NIBS) that has been found to affect both cognitive and physical performance. This study investigates the effects of a-tDCS targeting the left DLPFC (L-DLPFC) on endurance performance. We hypothesize that the stimulation enhances the performance.